Minimal surfaces - Кірноз, Ірина Анатоліївна; Корольов, Євген Олександрович; Корольов, Марк Євгенович (Eastern-European Journal of Enterprise Technologies, 2013)
Studying the minimal surfaces, we can gain the skills of their building, which is the main goal of our work. The objects of study are surfaces and graphics. The relevance of the work consists in the fact that the results can be the basis for writing other works and can be applied in various fields of activity. The article analyzes the experiments of Plato with soap films, which in this or that way are connected with minimal surfaces. The conclusion of the experiments, based on the presented model of graphs stimulated the emergence of a significant research area, developing up to these days and known under the title - the Plato problem. The further use of the skills acquired during the writing of this article can be implemented in the future, while working on building of surfaces. Our work is the visual aid of how the knowledge of the minimal surfaces in one area can become a reliable assistant in many other areas of our activity, in case of competent use of acquired skills